Temperature‐induced structural change of integrin αvβ3 receptor and its interaction with the RGD peptide ligand. Issue 2 (28th December 2022) - Wang, Anqi; Yue, Kai; Wei, Yiang; Zhong, Weishen; Zhang, Genpei
Abstract: The structural change of receptor protein at high temperatures is one of the factors affecting the targeting ability of ligand‐installed nanocarriers for combined therapy of hyperthermia and drug delivery. In this study, the binding behaviors and mechanisms of integrin αvβ3 receptor and the arginine‐glycine‐aspartic acid (RGD) peptide ligand at high temperatures were investigated both theoretically and experimentally. The structural parameters of integrin αvβ3 at different temperatures and the interaction forces between the RGD peptide and integrin αvβ3 at different binding sites were calculated by molecular dynamics simulation. Fourier transform infrared spectroscopy, energy dispersive spectroscopy, ultraviolet–visible absorption spectroscopy, and atomic force microscopy were used to analyze the structural changes of integrin αvβ3 and to measure the ligand‐receptor interaction. Results show that the number of hydrogen bonds decreased and the secondary structure of integrin αvβ3 changed with the increase in temperature, indicating the denaturation of integrin αvβ3. The structural stability of the integrin αv subunit was better than that of the integrin β3 subunit at high temperatures. The interaction between the RGD peptide and integrin αvβ3 weakened as the temperature increased because the structure of the integrin αvβ3 binding site became more flexible and the corresponding calcium ions were shed from the binding site. The strongest interaction force was exhibited at the binding site of the integrin β3 subunit at 310 K while it was found at the binding site of the integrin αv subunit at higher temperatures, owing to the smaller structure deformation of the integrin αv subunit. Abstract :